Neurofibromatosis Type 2 Presenting as Symptomatic Gallbladder Hydrops: A Rare Case Report and Literature Review - Bassel Hafez; Joudie Sahar Alwan; Walid El Hout; Karim Koussa; Tamara El Annan; Dolly Noun; Ahmad Zaghal (Wiley, 2024)
Neurofibromatosis type 2 (NF2), also known as NF2-related schwannomatosis (SWN), is a rare dominantly inherited genetic disorder mainly characterized by the presence of vestibular schwannomas (VSs) in addition to a range of other tumors that affect both the central and peripheral nervous systems. These tumors include cranial, spinal, peripheral nerve, and intradermal schwannomas, cranial and spinal meningiomas, and intrinsic central nervous system (CNS) tumors, usually spinal ependymomas. Juvenile cataracts are also common in patients with NF2, with most symptoms at presentation being hearing loss and visual disturbances. We present the case of a previously healthy 12-year-old girl who presented with postprandial right upper quadrant pain and was found to have a large hydrops of the gallbladder on ultrasound scan of the abdomen. Pathology of the gallbladder post laparoscopic cholecystectomy showed diffuse involvement of the gallbladder by a benign nerve sheath tumor that was suggestive of schwannoma. Further testing confirmed the diagnosis of NF2. This case helps shed light on unusual NF2 symptoms and underscores the importance of recognizing atypical presentations for timely intervention and management. It also adds value to a multidisciplinary approach in diagnosing and managing NF2.